Establishing hydrodynamic connectivity of Tonle Sap Lake and Mekong River through field measurements, remote sensing observation and modelling of Tonle Sap River - Sokly Siev (College of Engineering, University of the Philippines Diliman, 2014)
Due to the hydrodynamic and ecological significance of the flow reversal phenomenon between Tonle Sap Lake (TSL) and Mekong River (MR) through Tonle Sap River (TSR), there is a need to understand and model the hydrodynamic connectivity. In this study, analysis of satellite imagery was used to describe the unique reversal hydrology in term of water and sediment fluxes of TSR. First, a monthly time series from the Moderate Resolution Imaging Spectrometer(MODIS) satellite senor from 2003 to 2004 were acquired and processed to extract the water inundation, volume and flow direction. The flow between MR and TSL in modulated by the inflows coming into the TSR in addition to those water bodies. Soil Water Assessment Tool(SWAT) was applied to Chinit stream, one of the TSR catchments, to model its water discharge and sediment load with daily and monthly time step, respectively. The Nash-Sutcliffe coefficient(NSE) and coefficient of determination (R2 ) were used to evaluate SWAT model result.The calibration achieved NSE of 0.81 and R2 of 0.81 for the water discharge and NSE of 0.75 and R2 of0.76 sediment load while the validation achieved NSE of 0.85 and R2 of 0.85 for water discharge and NSE of 0.79 and R2 of 0.82 for the sediment load.The calibrated parameters were then applied remaining ungauged catchments within TSR watershed.A detailed model of CAESAR LISFLOOD (CL) were also used to estimate the flood sediment erosion, transport and erosion within the TSR by incorporating the calibrated and validated catchments boundary condition for the period of analysis of SWAT model. The CL results the simulation of the exchange flow between MR and TSL via TSR were compared with the time series concentrations based on MOD09Q1. The accuracy F was used the agreement between water surface area of CL and MOD09Q1. The accuracy F obtained from 13% to 70%. The river connectivity analysis was supported by comparing the water level data with elevation of river's bed change due to sedimentation of CL results.This analysis determined the percentage of persistent water indicated the degree connectivity of TSR in terms of water and sediment fluxes.